Atomic force microscope tip cleaning by using gratings as micro‐washboards. Issue 11 (2nd September 2013) - Shi, Bin; Zhang, Dongxian; Zhang, Haijun; Sang, Qing
ABSTRACT The sharpness of atomic force microscope (AFM) tips is essential for acquiring high quality AFM images. However, AFM tips would easily get contaminated during scanning and storage at ambient condition, which influences image resolution and causes image distortion. Replacing the probe frequently is a solution, but uneconomical. To solve this problem, several tip cleaning methods have been proposed but there is space for further improvement. Therefore, this article developed a method of tip cleaning by using a one‐dimensional grating (600 lines/mm) as a micro‐washboard to "wash" contaminated tips. We demonstrate that the contaminants can be scrubbed away by rapidly scanning such micro‐washboard against the tip in the aids of Z‐dithering (10–20 Hz) exerted on the washboard. This method is highly efficient and proved to be superior to traditional ones. Experiments show that AFM images acquired with "washed" tips have higher resolution and less distortion compared with images acquired using contaminated tips, even comparable to those scanned by new ones. Microsc. Res. Tech. 76:1131–1134, 2013. © 2013 Wiley Periodicals, Inc.